(3GdeGdjI GdYGeI GdfXe GdVQjHjI hehGRfI GdOhdIs - (3ahRj(B, (3YWhjs ((3HjQhJ(B:s (3efThQGJ GdMdHj(B,s, 2003)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3GdfXe GdVQjHjI,GdeGdjI GdYGeI h GdJTQjYGf GdeGdj h GdVQjHj,JWhQ GdfXGe GdVQjHj aj dHfGf,eaghe GdhGQOGJ GdYGeI,CfhGY GdhGQOGJ GdYGeI,eaghe GdVQGFH h NUGFUgG,GdCfXeI GdVQjHjI h CfhGY GdVQGFH,GdVQGFH GdeHGTQI h GdVQGFH ZjQ GdeHGTQI,GdVQjHI Ydi GdbjeI GdeVGaI,GdQShe h GdhGQOGJ GdYGeI,GdbQhV GdYGeI,GdEUOGQ GdfbOj GdLOjO,GdVQGFH GdeHGTQI h GdQShe GdeeGKdI dgG aj dHfGf,GdVQGFH ZjQ GdeHGTQI h GdQShe GdeeGKdI dgG aj dHfGf,JMUjd GdVQGFH h GdQShe,GdEROhGL GdVQjHj,GdJgQH ef GdVQGFH,ehGRfI GdOhdI,GdSjGSI GdeGdjI,NUGFU GdehGRfI GdYGeI,GdbhGYO GdYGeI dEYOGO GdehGRfI,ehGWf GdTPhP Yf fgL GdehGRfI GdJbdjOjI,GdLhGfH GdafjI dObI JbOjQGJ GdehGRfI GdYGeI,GdehGRfI GdYGeI aj dHfGf,GdEJLGgGJ GdMOjKI ddehGRfI GdYGeI,GdehGRfI h eJWdHGJ GdJNWjW GdEbJUGOj,GdSjGSI GdeGdjI h GdfXGe GdeGdj h GdVQjHj GdLOjO,GdEUdGM GdeGdj ef NdGd GdehGRfI GdYGeIs
(3HjHdjhZQGajG U(B.339s
Keywords: (3GdVQGFHs; (3GdeGdjI GdYGeIs; (3GdejRGfjIs; (3ehGRfI GdOhdIs; (3hQOGJs